GENETIC DIVERSITY OF INDONESIAN SHALLOTS BASED ON BULB-TUNIC PATTERNS AND MORPHOLOGICAL CHARACTERS - Lina Herlina; Reflinur Reflinur; Sobir Sobir; Awang Maharijaya; Suryo Wiyono; Bonjok Istiaji (Indonesian Agency for Agricultural Research and Development, 2019)
Variation within bulb tunics has been used to determine the genetic diversity in Allium species, including shallots. However, no such study has been reported for shallots of Indonesia. The study aimed to analyze the genetic diversity of the Indonesian shallots based on the bulb-tunic patterns. Thirty-five shallot genotypes from main production centers in Indonesia were used. The ultrasculptures of the bulb tunics were examined by light microscopy, including the inner surface and cell shape patterns of the bulb tunics. The phenotypic data, i.e. quantitative and qualitative traits were subjected to the descriptive statistics, principal component, correlation, regression, and clustering analyses. The results showed that the bulb-tunic cell patterns were varied, which shared almost identical with 13 Allium species. Total bulb weight per genotype showed the greatest variation (cv = 89.10%) and significant correlation with bulb weight per plant (r = 0.773). The principle component analyses showed the cumulative proportion of 78% of the total morphological variation in all shallot genotypes. Based on clustering analysis, the genetic variation of Indonesian shallots are grouped into twelve clusters with 50% genetic similarity. The study indicates that Indonesian shallots are genetically varied and could be useful for further utilization in their genetic improvement program.